CARACTERISTICA ARTICULATORIE A SUNETELOR COMPUSE ÎN LIMBA GERMANĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2011)
The article presents a study of dinamic-articulatory characteristics of the german diphthongs ['ae] ['ao] and ['oø]. On X-rays results the articulation of these diphthongs is described according to 7 gradual continuums. The unity of the components of the diphthongs is described as well. The articulatory characteristics of the diphthongs ['ae] ['ao] and ['oø] show that they are monophonemic.